Low pH, Aluminum, and Phosphorus Coordinately Regulate Malate Exudation through GmALMT1 to Improve Soybean Adaptation to Acid Soils(1)([W])([OA]) - Liang, Cuiyue (American Society of Plant Biologists, 2013)
Low pH, aluminum (Al) toxicity, and low phosphorus (P) often coexist and are heterogeneously distributed in acid soils. To date, the underlying mechanisms of crop adaptation to these multiple factors on acid soils remain poorly understood. In this study, we found that P addition to acid soils could stimulate Al tolerance, especially for the P-efficient genotype HN89. Subsequent hydroponic studies demonstrated that solution pH, Al, and P levels coordinately altered soybean (Glycine max) root growth and malate exudation. Interestingly, HN89 released more malate under conditions mimicking acid soils (low pH, +P, and +Al), suggesting that root malate exudation might be critical for soybean adaptation to both Al toxicity and P deficiency on acid soils. GmALMT1, a soybean malate transporter gene, was cloned from the Al-treated root tips of HN89. Like root malate exudation, GmALMT1 expression was also pH dependent, being suppressed by low pH but enhanced by Al plus P addition in roots of HN89. Quantitative real-time PCR, transient expression of a GmALMT1-yellow fluorescent protein chimera in Arabidopsis protoplasts, and electrophysiological analysis of Xenopus laevis oocytes expressing GmALMT1 demonstrated that GmALMT1 encodes a root cell plasma membrane transporter that mediates malate efflux in an extracellular pH-dependent and Al-independent manner. Overexpression of GmALMT1 in transgenic Arabidopsis, as well as overexpression and knockdown of GmALMT1 in transgenic soybean hairy roots, indicated that GmALMT1-mediated root malate efflux does underlie soybean Al tolerance. Taken together, our results suggest that malate exudation is an important component of soybean adaptation to acid soils and is coordinately regulated by three factors, pH, Al, and P, through the regulation of GmALMT1 expression and GmALMT1 function.